A Skewness Fitting Model for Noise Level Estimation and the Applications in Image Denoising. Issue 1 (April 2021) - Zhou, Bin; Zhong, Biying; Feng, Jun
Abstract: In this paper, a novel noise level estimation technique is presented based on skewness fitting. The difference between exact skewness and observed value on each channel contributes to an objective function. The skewness concentration is helpful to guarantee the reasonability of the model. The optimal solution means an estimation of the noise variance and it is easy to be applied in some parametric denoising model. The accuracy and efficiency of proposed algorithm were verified by the numerical experiments.